The relationship of soluble p‐tau isoforms with brain amyloid and tau deposition in sporadic AD. (20th December 2022) - Barthélemy, Nicolas R.; Saef, Benjamin A.; Li, Yan; Gordon, Brian A.; He, Yingxin; Horie, Kanta; Sato, Chihiro; Ovod, Vitaliy; Benzinger, Tammie L.S.; Morris, John C.; Bateman, Randall J.; Schindler, Suzanne E.
Abstract: Background: Hyperphosphorylated tau isoforms (p‐tau) in cerebrospinal fluid (CSF) and plasma represent promising measures to monitor Alzheimer disease (AD) pathological changes. Brain amyloid deposition precedes tau aggregation and associated clinical decline by two decades. Several CSF and plasma p‐tau isoforms have been described as potential surrogates for tau Positron Emission Tomography (PET) imaging, but p‐tau isoforms have a strong association with amyloid PET, and increase without tau pathology. In this study, we investigated the relationship between multiple CSF p‐tau isoforms and brain imaging measures in the Knight ADRC cohort. Method: We analyzed 10 p‐tau isoforms by mass spectrometry in 1932 CSF samples (1173 participants). Associated data includes 1250 amyloid PET and 442 tau PET scans, as well as CSF Aβ42/Aβ40 by immunoassay for all samples. We measured phosphorylation occupancies (ptau/tau) at T111, T153, T175, T181, S199, S202, T205, S208, T217 and T231, together with corresponding p‐tau and tau concentrations. We compared the accuracy of CSF p‐tau isoforms in predicting amyloid PET and tau PET status stratified according to amyloid PET, tau PET and/or Clinical Dementia Rating (CDR) status. Results: PT217/T217 best‐predicted abnormal amyloid PET (AUROC=0.980) or CSF Aβ42/Aβ40 (AUC=0.954). PT217/T217 predicted brain amyloidosis in asymptomatic and symptomatic participants with similar accuracy (AUC=0.979 and 0.986 respectively) and was correlated with amyloid PET centiloid and CSF Aβ42/Aβ40 (Spearman R=0.73 and ‐0.76, p<0.0001). Notably, the correlation between pT217/T217 and amyloid PET centiloid was higher in amyloid PET(+)/tau PET(‐) compared to amyloid PET(+)/tau‐PET(+) (R=0.77, p<0.0001 versus 0.16, p=0.007). PT205/T205 and pT217/T217 better predicted tau PET positivity in amyloid PET(+)positive participants (AUC=0.908 and 0.866). These markers were also associated with tau PET signal in tau PET(+) participants (R=0.53 and 0.55 p<0.0001). Other p‐tau isoforms also predicted amyloidosis, except for T175, S199, S202 and T205. Only pT205/T205 and pT217/T217 were correlated with tau‐PET in tau PET(+) participants. Conclusion: These results suggest that tau hyperphosphorylation, notably at T217, is more strongly associated with brain amyloid burden than tau deposition in tau PET(‐) individuals. After tau PET becomes positive, p‐tau217 and p‐tau205 are correlated with tau burden. Soluble p‐tau are markers of both amyloid and tau aggregation in the AD brain.